Evaluation and reporting of CSR in SME sector - Szczanowicz Justyna; Saniuk Sebastian (Management, 2016)
This article is an attempt to propose a CSR evaluation and CSR reporting model in small and medium-sized enterprises. Special attention was given to trends which reveal the need for CSR development in practice with particular emphasis on efficiency - understood in two aspects: first one related to social welfare and sustainable development and the second one as a competitive advantage.